A agricultura familiar no norte do Rio Grande do Sul - região da AMAU (1950-2021) : potencialidades e limites de seu desenvolvimento sustentável - Zanella, Anacleto (2022)
This research is characterized by an analysis of the development process of family-based agriculture, between 1950 and 2021, in the region of the Association of Municipalities of Upper Uruguay (AMAU), in the north of Rio Grande do Sul – a territory historically characterized by the decisive participation of this sector in its expansion process. In the current context, in which Brazil and the world are experiencing acute crises – food insecurity (hunger expansion), sanitary (Covid-19 pandemic) and climate (global warming), among others – this study gains relevance because it discusses the multifunctional role of family agriculture, especially for the production of healthy foods and for the preservation of natural resources in rural areas. Based on the concept of sustainable development defined in the 2030 Agenda by the United Nations (UN), the research has as its central objective the debate on the following question: what are the main potentialities and limits of the sustainable development of family agriculture in the present time and in three dimensions - economic, social and environmental - taking into account both its historical trajectory and the recent context? The development of the research took place through literature review, systematization of information collected by the Brazilian Institute of Geography and Statistics (IBGE), collection of news in local newspapers, application of descriptive questionnaire and oral interviews with farmers (young people and adult) and leaders of unionism and social movements. The paper argues that some historical contradictions (such as prioritization of European immigrant peoples or their descendants and the deprecation of indigenous, black and caboclos peoples; the unequal distribution of land; the process of conservative modernization of agriculture that favored better-capitalized farmers) and more recent ones (such as the exodus of young people swells and the aging of the rural population; the concentration of public policies, production and agricultural income among consolidated farmers; the advance of the conventional model and production of agricultural commodities in deprecation to healthy foods) block the full sustainable development of family farming in this region. Despite these vigorous limits/contradictions, the research points out that, in the context of the present time in which there is a need to expand the production of healthy foods and to face the climate crisis, family farming, especially in this region, has some unique potentialities - its multifunctional role, its enormous representation and its strong organizational tradition (unionism, social movements and cooperativism) - that allow the development of an agenda that mobilizes broad social sectors in order to put family farming back at the center of the Public Policies of the Brazilian State and to contribute decisively in the perspective of the implementation of the UN 2030 Agenda, especially in this territory.